Luminex xMAP Assay to Quantify Cytokines in Cancer Patient Serum - Kupcova Skalnikova, Helena; Vodickova Kepkova, Katerina; Vodicka, Petr (Methods in molecular biology (Clifton, N.J.), 2020)
Cytokines, chemokines, and growth factors are key mediators of cell proliferation, migration, and immune response, and in tumor microenvironment, such factors contribute to regulation of tumor growth, immune cell recruitment, angiogenesis, and metastasis. In body fluids, levels of inflammatory mediators reflect the patient immune response to the disease and may predict the effects of targeted therapies. Significant improvements in cytokine detection techniques have been made during last 10 years leading to sensitive quantification of such potent molecules present in low pg/mL levels. Among the techniques, Luminex xMAP® multiplex assays allow for simultaneous quantification of up to 100 analytes with high sensitivity, broad dynamic range of quantification, high throughput, and minimal sample requirements. In this chapter we describe a detailed protocol for the application of xMAP assays using Luminex® 200™ analyzer with xPonent® acquisition software to quantify cytokines, chemokines, and growth factors secreted to blood serum and plasma of cancer patients. We also discuss how sample preparation, instrument settings, and standard curve fitting algorithms can influence validity of obtained results. Special attention is paid to data analysis using open source R statistical environment and we provide an example dataset of cytokine levels measured in serum and corresponding R script for standard curve fitting and concentration estimates.
Keywords: Immunoassay; luminiscenční měření; drLumi; Cytokines; biologické markery; nCal; Biomarkers; Multiplex xMAP assays; R Bioconductor; Neoplasms; nádory; Luminex 200; cytokiny; software; lidé; Cancer; analýza dat; Algorithms; Plasma; imunoanalýza; algoritmy; Serum; Software; xPonent software; Cytokine; Luminescent Measurements; Data Analysis; Humans